(untitled) (Annals of Bangladesh Agriculture, 2019)
Gastrointestinal parasitic infections are considered as one of the major impediments in profitable livestock farming in subtropical and tropical countries. The present study was carried out to investigate the prevalence of gastrointestinal (GI) parasites and to determine the effects of different factors in the occurrences of GI parasitic infections in calves. A cross-sectional study, including 413 fecal samples from calves, was conducted in Pabna, Sirajgonj and Gazipur districts of Bangladesh. The samples were examined using standard coprological techniques like sedimentation and floatation techniques, and lugol’s iodine and modified Ziehl-Neelson staining. The overall prevalence of gastrointestinal parasitism was 45.3% and commonly identified parasites were Toxocara spp. (20.3%), Strongyloides spp. (3.9%), Fasciola sp. (1.0%), Moniezia spp. (1.5%), Giardia sp. (10.4%) and Cryptosporidium spp. (7.0%). Among the factors, the age, sex and health status had significant effects on the GI parasitic infections in calves. Therefore, special care such as routine fecal examination for parasitism and proper deworming program should be taken to maintain good health and husbandry of calves for profitable livestock production. Ann. Bangladesh Agric. (2019) 23(2) : 1-13